A new understanding of health related empowerment in the context of an active and healthy ageing - Lars Kayser; Astrid Karnoe; Emily Duminski; David Somekh; Cecilia Vera-Muñoz (BMC, 2019)
Abstract Background Recently, several initiatives have focused on how to create true person-centred health services. This calls for a new understanding of health-related empowerment in relation to people living with one or more chronic conditions. We report on a Delphi investigation among participants in the European Innovation Partnership on Active and Healthy Ageing that has led to a new understanding of health-related empowerment. Methods The Delphi process was conducted in three sequential rounds. In the first round, we presented a suggested first version for a definition of "health-related empowerment" divided into nine statements. One hundred and twenty-two experts were then asked if they agreed or not with each individual statement, and in the case they disagreed, to state the reasons for their disagreement. After revisions, the experts who had replied to the first version were asked again, if they agreed or not with each individual statement of the second version and to elaborate on disagreements. Finally, in the third round the experts were asked to provide comments to the final proposed definition in general and not by each statement. Results A total of 33 experts responded to the first version. The following revision included a merging of two statements, and the addition of health literacy as part of the understanding. The second version was sent out to the 33 experts and a total of 19 experts commented with moderate consensus. Changes included removal of "self-esteem" and change of "self-confidence" to confidence. Third version was sent out to all 122 experts with 16 respondents. Strong consensus was obtained for this third version, and is with one minor change presented as the final version. Conclusion We propose a new understanding of the concept health-related empowerment, by focusing on the individual as a co-manager with freedom to choose and focus on their own well-being.